Bowling and self-handicapping the effects of self-efficacy, feedback and sex. - Hormillosa, Celeste Joy J.
Seventy (70) students enrolled during the Second Semester 1998-1999 at the University of the Philippines in the Visayas were participants in a correlational and experimental study which aimed to know whether self-efficacy, feedback and sex affect self-handicapping, and if self-handicapping influences performance. The Pearson product moment correlation coefficient result showed that self-efficacy had no significant relationship with self-handicapping. The chi-square test revealed that feedback did not affect self-handicapping as well. Chi-square test for sex vis-a-vis self-handicapping showed no significant relationship. The t-test using a self-handicapping scale showed that males self-handicapping to have no influence on performance. However, the data from the self-handicapping scale showed that high self-handicappers performed better than low self-handicappers.